Effect of moisture on the curing and processing behaviour of an epoxy underfill system - Lim, Sin Heng. (2008)
This project sought to evaluate two cases of water contamination on the processing behaviour and the thermo-mechanical properties of an anhydride cured cycloaliphatic epoxy resin commonly used in underfill formulations. In this study, known amounts of water were deliberately introduced into underfill system via two different routes as to simulate two possible ways that water can be introduced to the underfill system, namely (a) during production stage, and (b) during storage and formulation stage. In order to simulate the first case of contamination, water was added directly to the formulated underfill system. As for the second case, water was added directly to the epoxy resin before formulation.